Dynamic Characterization of III-Nitride-Based High-Speed Photodiodes - Bandar Alshehri; Karim Dogheche; Sofiane Belahsene; Abderrahim Ramdane; Gilles Patriarche; Didier Decoster; Elhadj Dogheche (IEEE Photonics Journal)
The objective of this study is to study, design, and develop a high-speed PIN photodiode based on InxGa 1-xN/GaN alloys deposited by metal–organic chemical vapor deposition. The configuration used for the PIN photodiode is based on an absorbing layer composed of In0.1Ga0.9N multiple quantum wells. Structural, microstructural, and optical analyses have been carried out using TEM, PL, and absorption measurement. The design of PIN structures varies with an active surface ranging from $10^{4}\,{\rm{to\,10}}^{6}\,{\rm{μ m}}^{2}$ . Static and dynamic characterizations have been performed to qualify the photodiode response. A photocurrent value reaching a maximum of 1.2 mA is reported for a diode of ${\rm{100× 100\,μ m}}^{2}$ area, with an external quantum efficiency of 13%. Using the noise measurement technique, the device reveals a −3-dB cutoff frequency of 300 MHz for the same photodiode. This result clearly shows the potential of III-nitride materials for targeting high-speed optoelectronics. The future prospect is to work toward InGaN-based microphotodiodes in order to achieve optical transmission links in the UV-visible range using the same material system.